Ecologia e comportamento della lontra eurasiatica (Lutra lutra) in un'area mediterranea (Alentejo, Portugal) - QUAGLIETTA, LORENZO (Università degli Studi di Roma "La Sapienza", 2012)
Despite being a highly studied carnivore, the Eurasian otter (Lutra lutra) still offers the opportunity to explore many aspects of its ecology and behaviour that are poorly known or have only been investigated in temperate areas. From April 2007 to October 2010, the OPA research project (Otter Project in Alentejo) was conducted in the south-central Alentejo region of Portugal, in an area of roughly 800 km2. Through the capture and subsequent radio-tracking of 16 wild Lutra lutra individuals (9 males and 7 females) for an average of 139 radio-locations per animal (about 126 days), together with the genotyping of 51 individual otters, the project aimed to provide a set of basic data on the biology and ecology of the species that were missing or limited throughout its extent of occurrence or in the Mediterranean environment. This thesis focus on some of the aspects of the referred project, such as: (1) extent of home ranges (HR) and movement patterns, including their relationships to seasonality and the availability (and its variability) of water resources; (2) genetic spatial structure, dispersal and social interactions; (3) activity rhythms; (4) habitat selection, with particular focus on the modality and frequency of use of reservoirs; (5) testing of a GPS GSM/GPRS telemetry system in riparian habitats and on free-ranging wild otters. Concerning point (1), Network K-function analyses revealed a non-uniform use of home ranges in all monitored individuals of adult size, thus showing fidelity to their annual home range (site fidelity). On average, 49 radio-locations (fixes) (corresponding to approximately 45 days of tracking) were necessary to estimate a stable home range. The estimated average linear extension of home ranges was approximately 16.8 km for females (SE = 2.8) and 38.5 km for males (SE = 2.4), or 22.5 and 92.7 Ha respectively. The maximum extension recorded was 68.1 km (78.6 km including outliers). All individuals had at least one artificial reservoir within their home ranges, representing, on ...